Perceptions of Maternal Discrimination and Pregnancy/Postpartum Experiences Among Veterinary Mothers - Wayne, Annie S.; Mueller, Megan K.; Rosenbaum, Marieke (Frontiers in Veterinary Science, 2020)
Objective: To describe rates of maternal discrimination among veterinary mothers. Design: Cross-sectional and mixed-methods online anonymous survey posted to a social media platform closed group “Moms with a DVM”. Sample: 1,082 veterinarian mothers. Procedures: The online survey included a combination of closed and open-ended questions regarding perceived discrimination, inequities in the work-place due to pregnant or maternal status, desired accommodations and questions regarding timing of pregnancy(ies) and fertility issues. Results: At least on form of perceived discrimination was reported by 819 (75.7%) respondents (M = 2.6, SD = 2.1, range 0-10). Specifically, 789 (72.9%) reported maternal discrimination. Over half of the sample (n = 632, 58.4%) reported at least one instance of perceived inequity in the workplace due to status as a mother (M = 1.23, SD = 1.4, range 0-5). A majority (906, 83.7%) reported that their career had “definitely” or “maybe” affected the timing of their children. A subset of respondents, 189 (17.5%) experienced at least one miscarriage, and 192 (17.6%) used fertility treatment due to difficulty conceiving. Postpartum depression was diagnosed in 181 respondents (16.7%), and 353 (32.6%) reported symptoms consistent with postpartum depression but did not seek medical care. Of 953 participants who needed accommodations for breastfeeding and/or pumping while at work, 130/953 (13.6%) reported excellent accommodations, 454/953 (47.6%) adequate, 258/953 (27.1%) inadequate, and 111/953 (11.6%) had no accommodations provided. Conclusions and Clinical Relevance: High rates of perceived maternal discrimination are documented and highlight the need for attention and changes to ensure veterinarians have supportive and sustainable career options.